MATHEMATICAL MODEL OF WOOD SAWING ACCURACY ON HORIZONTAL BAND SAW MACHINES - Pylypchuk, M.I.; Shostak, V.V.; Stepanchuk, S.P.; Rebezniuk, I.T.; Lazarchuk, K.; Salovskyy, S.; Salun, M. (Forestry, Forest, Paper and Woodworking Industry, 2018)
Creation of the mathematical model of wood sawing accuracy on the horizontal band saw machines and its realization as an application program on a computer will enable to predict the accuracy of sawing, to determine effective ways of its increasing and to automate the regulation of cutting modes on these machines. Develop a mathematical model for the accuracy of wood sawing on the horizontal band saw machines to determine the nature of the influence of factors and find effective methods for increasing the accuracy of sawing. The energy method, the methods of analytical mechanics for determining forces acting on the saw, and the finite element method for studying the stiffness of the band saw using 3D modeling were used. The mathematical dependence of the accuracy of wood sawing on the horizontal band saw machines was established, on the basis of which the analysis of the influence a set of factors on the accuracy of sawing was made and methods of its increasing were determined. The obtained mathematical model of the accuracy of sawing of wood on the horizontal band saw machines allows to determine the value of sawing waviness, to establish rational modes of cutting of wood and to carry out automated regulation of sawing modes on machine tools.